Nova (2007), volume 4 ebook Nova corps. - Abnett, Dan (Nova (2007), 2012)
Collects Nova #19-22. Could it be --the return of the Nova Corps? Will things ever be the same for Richard Rider? What is the Worldmind up to, and what will it mean for the future of the Human Rocket and the Nova Corps itself?! Author: Dan Abnett, Andy Lanning. Illustrator: Wellington Alves. © 2019 Marvel Characters, Inc. All rights reserved. All characters featured in this issue and the distinctive names and likenesses thereof, and all related indicia are trademarks of Marvel Characters, Inc. No similarity between any of the names, characters, persons, and/or institutions in this magazine with those of any living or dead person or institution is intended, and any such similarity which may exist is purely coincidental. www.marvel.com.com